Birmingham's rabbi : Morris Newfield and Alabama, 1895-1940 - Cowett, Mark, 1951- (Judaic studies series (Unnumbered), 1986)
American Jewish history has been criticized for its parochial nature because it has consisted largely of chronicles of American Jewish life and has often failed to explore the relationship between Jews and other ethnic groups in America. Rabbi Morris Newfield led Temple Emanu-El in Birmingham from 1895-1940 and was counted among the most influential religious and social leaders of that city. Cowett chronicles Newfield's career and uses it as a vehicle to explore the nature of ethnic leadership in America. In doing so he explores the conflicts with which Newfield stru.